2017
DOI: 10.1007/s11060-017-2641-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of neutrophil–lymphocyte ratio in prognosis of glioblastoma multiforme

Abstract: Neutrophil-lymphocyte ratio (NLR) is a hematological marker of systemic inflammation and several studies demonstrate an association between a higher NLR and a worse prognosis in many malignancies. However, literature analyzing its prognostic value in glioblastoma multiforme (GBM) is still scarce. We intended to analyze the correlation of NLR with overall survival and progression-free survival in patients with GBM performing a retrospective review of the patients with diagnosis of GBM submitted to a resection s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 36 publications
5
76
3
1
Order By: Relevance
“…We did not find any statistically significant association between neutrophil, lymphocyte, or platelets or their ratios like NLR and PLR, as has been previously suggested in other studies in in solid tumors as well as in brain tumors, DLBCL, and PCNSL . A recent retrospective study analyzing the potential prognostic impact of NLR in a cohort of 62 patients with PCNSL showed that high NLR (≥2) was associated with poor prognosis in univariate analysis but not in multivariate analysis .…”
Section: Discussionsupporting
confidence: 62%
“…We did not find any statistically significant association between neutrophil, lymphocyte, or platelets or their ratios like NLR and PLR, as has been previously suggested in other studies in in solid tumors as well as in brain tumors, DLBCL, and PCNSL . A recent retrospective study analyzing the potential prognostic impact of NLR in a cohort of 62 patients with PCNSL showed that high NLR (≥2) was associated with poor prognosis in univariate analysis but not in multivariate analysis .…”
Section: Discussionsupporting
confidence: 62%
“…All of the included studies were published in recent years and were from seven different countries, which were retrospectively designed with 17 single‐center trialsand one multicenter trial . There were 15 studies performed multivariate Cox regression analysis and reported adjusted HR . The main features of the selected studies are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In the analysis of the NLR for predicting the prognosis of gliomas, 15 studies ( n = 2,798 patients) were included. The patients with a higher pre‐operative NLR had a worse prognosis (HR: 1.38; 95% CI: 1.09–1.74; P = 0.008; Figure a ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glioblastoma is an aggressive cancer type originating from astrocytes and is marked by high levels of neutrophilic inflammation 17 with high neutrophil-to-lymphocyte ratios and neutrophil activity correlating with enhanced tumor progression and poor patient outcomes 1820 , however little is known about neutrophil interaction with early transformed astrocytes in vivo . The zebrafish larval model allows for unparalleled non-invasive imaging of the early stages of tumor initiation as well as interactions between tumor-initiating cells and immune cells.…”
Section: Introductionmentioning
confidence: 99%